1977
DOI: 10.1203/00006450-197704000-00227
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Inorganic Lead on Isolated Rat Brain Mitochondrial Respiration

Abstract: In the ndult rat, fed 2, the activity of jejunal sucreae shows a diurnal rhythm with a peak during the dark period. Ontogenitally this enzyme doe^ not appear until approximately the 16th postnatal day; its activity then rises rapidly and re ache^ adult levels by the 35th day. Our aim was to determine whether the diurnal rhythm is present from the outset or appeers only after sucrase has attaine6 adult levels. Rat pups were raised in litters of 9 with a li~htldark cycle of l?.h. Solid food and water were availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1980
1980
1981
1981

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The concentration range of PbAc required to produce an inhibition of respiration was an order of magnitude (10 times) less than the lowest amounts used in previous studies. Holtzman et al (1978) found that at concentrations below 50 p~, PbAc did not appear to inhibit brain mitochondrial respiration. This may have been caused by the presence of Pi and 0.2 mM-EDTA in their incubation medium at the time of Pb2+ addition.…”
Section: Controlmentioning
confidence: 89%
See 1 more Smart Citation
“…The concentration range of PbAc required to produce an inhibition of respiration was an order of magnitude (10 times) less than the lowest amounts used in previous studies. Holtzman et al (1978) found that at concentrations below 50 p~, PbAc did not appear to inhibit brain mitochondrial respiration. This may have been caused by the presence of Pi and 0.2 mM-EDTA in their incubation medium at the time of Pb2+ addition.…”
Section: Controlmentioning
confidence: 89%
“…It was proposed by Holtzman et al (1978) that lead inhibits a step in the citric acid cycle substrate oxidation prior to NADH dehydrogenase, because NAD-linked substrates are more sensitive to the effects of lead. This appears to be supported from data obtained in the present experiments with selected substrates.…”
Section: Controlmentioning
confidence: 99%
“…Inhibition of the Pb-induced increase in respiration by Ruthenium Red supports the hypothesis that Pb2+ and Ca2+ share carrier or binding sites in brain mitochondria (Holtzman et al, 1978). La3+ inhibition of Pb2+ uptake suggests a similar analogy of Pb2+ and Caz+ uptake in rat heart mitochondria (Scott et al, 1971).…”
Section: Discussionmentioning
confidence: 60%
“…The effects of the concentrations of Pb(Ac), shown in Fig. 1 on cerebral mitochondrial respiration were the same as previously described (Holtzman et al, 1978). As shown in Fig.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation